Peran Pengendalian Keuangan dalam Pencairan Pembayaran Internal: Perspektif Akuntansi Syariah Bank BJB - Syifa Rahmatul Awaliyah; Mia Lasmi Wardiyah (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2026)
This study aims to analyze the role of the Financial Control Division in controlling the payment disbursement stage to internal divisions at the Head Office of Bank bjb Syariah. The research employed a descriptive qualitative approach, with data collected through interviews and direct observations conducted during the Field Work Practice (PKL). Data validity was ensured through source triangulation by comparing information from interviews, observations, and relevant literature. The results indicate that the Financial Control Division plays a significant role in the payment disbursement process through mechanisms of document verification, administrative completeness checks, and supervision of payment requests in accordance with applicable procedures. The implemented controls are intended to maintain administrative order, minimize the risk of errors, and prevent potential irregularities. These control mechanisms reflect the principles of Islamic accounting, particularly the principles of trustworthiness (amanah) and prudence. The study identifies incomplete documentation as a common challenge, which is addressed through a document return mechanism that allows the requesting division to complete the required documents. The findings provide implications for the development of internal control systems in Islamic financial institutions, demonstrating how Islamic accounting principles can be operationalized to enhance financial management practices while maintaining ethical and religious compliance standards.